Analisis Pemberitahuan Informasi Halal Pada Aplikasi Grab Food Menurut Kompilasi Hukum Ekonomi Syariah - Nasution, Putri Firyal Ariqah; Tarigan, Tetty Marlina (Fakultas Syariah INSURI Ponorogo, 2022)
Muamalah activities always keep up with the times, the influence of world globalization and increasingly sophisticated technology causes humans to demand fast and easy things in various fields of life. One of them is the food delivery service from Grab or commonly known as Grab Food. The use of technology and information systems makes food delivery services very efficient to use, namely by placing an order online through a smartphone application. However, it is very unfortunate that the notification of halal information in it is not as complete as the Grab application in the neighbor country. Therefore, the purpose of this writing is to make Grab and consumers aware of the importance of including halal information in every product they distribute in the community. In writing this article the method used by the author is to use a normative juridical method, namely, library research originating from various literature with discussions that are in accordance with the author's theme. The results of the study show that there are differences in the halal food selection feature already available in the Grab Malaysia application, but for the Indonesian application this feature is not yet available. So that many Muslim consumers are trapped and confused in choosing halal products. This is not in accordance with the rules contained in the Compilation of Sharia Economic Law.